The Neural Reality of Syntactic Transformations: Evidence from Functional Magnetic Resonance Imaging. - Ben-Shachar, Michal; Hendler, Talma; Kahn, Itamar (Psychological Science., 2003)
A study, using functional magnetic resonance imaging, was conducted to complement neuropsychological evidence on the functional anatomy of syntactic transformations, a major computational operation applied in sentence processing. The findings, which revealed that the neural processing of transformations is localizable because it evoked a highly lateralized and localized activation in the left inferior frontal gyrus as well as a bilateral activation in the posterior superior temporal sulcus, are important because they constitute the first clear-cut imaging evidence for the neural reality of syntactic transformations.